(untitled) (Annual of the Faculty of Philosophy in Skopje, 2010)
For many years, the educational system in the Republic of Macedonia was based on a unitary organizational and didactic-methodical structure. The school-subject system drafted by Jan Amos Komensky overcame the limitations of the previous undifferentiated individual concept of teaching in medieval schools. The four stages of work in the classroom and the evident display of the clear concepts of Pestalozzi, as well as the formal teaching degrees of Johann Friedrich Herbart, have for a long period of time played a significant role in conducting the teaching. However, they have all referred to a group, without any opportunity to grasp the individual characteristics of the pupils. Furthermore, the social and educational changes are moving forward in the direction of emphasis on individuality, specificities and differences. Hence the ever-growing need has arisen for their comprehension, respect, cultivation and development. It is from this point that requests for modification of the education in that direction have been sought after. Democratization as a social process has found its place in education as well. The tendency of the schools and the education to become accessible to the interests, needs, opportunities and affinities of every individual is being more and more clear and visible. The Republic of Macedonia with its specific social constellation is moving towards this global trend. The first private schools which have offered an educational concept quite different from the current one have already been opened. Their role in the development of the democratization of the education in our country is undoubtedly noteworthy and for this reason the need for their theoretical elaboration has arisen.